CRITICAL REVIEW OF LAW NUMBER 12 OF 2022 CONCERNING CRIMINAL ACTS OF SEXUAL VIOLENCE - Azhari, Aidul Fitriciada; Litti , Nur Lina Afifah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
This article aims to find out whether Law No. 12 of 2022 is it in accordance with Islamic law?, which will be answered in this research. The approach used is a normative approach, while this research is descriptive-analytic in nature. The type of data needed is secondary data by taking data sources from books or previous research results related to Islamic law and violence against women. From the results of this study it is known that Law no. 12 of 2022 adopts the principles of dar'ul mafasid muqaddammun 'ala jalbul mashalih contained in Islamic law, protecting society from damage and prioritizing goodness. Not only giving punishment to the perpetrators of violence, Law no. 12 of 2022 also provides protection to victims and fulfills their rights. This is in line with Islamic teachings, protecting human dignity.